2016
DOI: 10.1037/hop0000030
|View full text |Cite
|
Sign up to set email alerts
|

The future of the history of psychology in Argentina and Brazil.

Abstract: This article analyzes the development of the history of psychology in Argentina and Brazil, beginning with the emergence of the history of psychology at the beginning of the 20th century. The paper analyzes that such old historical reconstructions were written by the same authors or institutions that were introducing Psychology in the two countries. That is, the older historical productions in the field of psychology were Whig biased. An analysis of the last 30 years of history of psychology is also provided. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
12

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 45 publications
0
11
0
12
Order By: Relevance
“…b Because the course is offered on a semester basis and each half of the total enrollment takes the course in one of those semesters, technically the half of such ratio represents the number of students per auxiliary per semester (249 students for each auxiliary). developed in Argentina (Klappenbach & Jacó-Vilela, 2016), we can conclude that history courses' contents are to a large extent local contents: that is, scholarship about the history of Argentinian psychology. Scholars such as Pickren (2012) and Rutherford and Pickren (2015) have suggested that history of psychology courses should try to balance local, regional, and international contents with the aim of internationalizing the curriculum and conveying a complete picture of the discipline's multiple origins and developments.…”
Section: Results and Discussion First Stage: Bibliometric Analysis Ofmentioning
confidence: 94%
See 2 more Smart Citations
“…b Because the course is offered on a semester basis and each half of the total enrollment takes the course in one of those semesters, technically the half of such ratio represents the number of students per auxiliary per semester (249 students for each auxiliary). developed in Argentina (Klappenbach & Jacó-Vilela, 2016), we can conclude that history courses' contents are to a large extent local contents: that is, scholarship about the history of Argentinian psychology. Scholars such as Pickren (2012) and Rutherford and Pickren (2015) have suggested that history of psychology courses should try to balance local, regional, and international contents with the aim of internationalizing the curriculum and conveying a complete picture of the discipline's multiple origins and developments.…”
Section: Results and Discussion First Stage: Bibliometric Analysis Ofmentioning
confidence: 94%
“…Regarding other contextual factors, Argentinian history courses count with certain strengths and advantages, the most important being the training of regular, adjunct, and auxiliary professors. During the 1990s, research groups on historical subjects formed in psychology programs (Klappenbach & Jacó-Vilela, 2016). Most researchers at those groups are also teachers at history undergraduate courses.…”
Section: Second Stage: Qualitative Analysis Of Procedures and Structurmentioning
confidence: 99%
See 1 more Smart Citation
“…La producción historiográfica indica que los historiadores de la psicología suelen historiar sobre la psicología de su propio país ( Klappenbach & Jacó-Vilela, 2016;Klappenbach & Fierro, 2016). A la vez, la historiografía de la psicología iberoamericana suele ser comunicada y difundida por autores iberoamericanos (Carpintero, 2007).…”
Section: Predominio De Autores Argentinos Y Sus Implicanciasunclassified
“…A razão de ser dessa escolha, a partir dos saberes psi aplicados ao campo do trabalho, se deve ao fato de que grande parte dos estudos de história da psicologia nesse período privilegia a escola ou a clínica médica, por serem domínios e campos de ação melhor estruturados, no Brasil dessa época (Pereira & Pereira Neto, 2003;Figueira & Boarini, 2014;Klappenbach & Jacó-Vilela, 2016; Jacó-Vilela, Espírito-Santo, Degani-Carneiro, Goes, & Vasconcellos, 2016). Aqui, no entanto, buscou-se um ângulo distinto.…”
Section: Introductionunclassified